Alternative Functional rad21 Paralogs in Fusarium oxysporum - Pareek, Manish; Almog, Yael; Bari, Vinay Kumar; Hazkani-Covo, Einat; Onn, Itay; Covo, Shay (Frontiers in Microbiology, 2019)
Cohesin, the sister chromatid cohesion complex, is an essential complex that ensures faithful sister chromatid segregation in eukaryotes. It also participates in DNA repair, transcription and maintenance of chromosome structure. Mitotic cohesin is composed of Smc1, Smc3, Scc3 and Rad21/Mcd1. The meiotic cohesin complex contains Rec8, a Rad21 paralog and not Rad21 itself. Very little is known about sister chromatid cohesion in fungal plant pathogens. Fusarium oxysporum is an important fungal plant pathogen without known sexual life cycle. Here, we describe that F. oxysporum encodes for three Rad21 paralogs; Rad21, Rec8 and the first alternative Rad21 paralog in the phylum of ascomycete. This last paralog is found only in several fungal plant pathogens from the Fusarium family and thus termed rad21nc (non-conserved). Conserved rad21 (rad21c), rad21nc and rec8 genes are expressed in F. oxysporum although the expression of rad21c is much higher than the other paralogs. F. oxysporum strains deleted for the rad21nc or rec8 genes were analyzed for their role in fungal life cycle. Δrad21nc and Δrec8 single mutants were proficient in sporulation, conidia germination, hyphal growth and pathogenicity under optimal growth conditions. Interestingly, Δrad21nc and Δrec8 single mutants germinate less effectively than wild type strains under DNA replication and mitosis stresses. We provide here the first genetic analysis of alternative rad21nc and rec8 paralogs in filamentous fungi. Our results suggest that rad21nc and rec8 may have a unique role in cell cycle related functions of F. oxysporum.